120 A NOVEL YEAST ASSAY FOR MEASURING HORMONE LEVELS. (1st January 2005) - Sandrock, T.; Terry, A.; Stillman, D.; Meikle, A. W.
Abstract : Introduction: Hormone receptors contain domains that regulate their nuclear localization and ability to activate transcription. We have developed a yeast bioassay that relies on the interaction of an agonist with a hormone receptor ligand-binding domain (LBD) to affect transcription of a reporter gene. Methods: The LBD of the human androgen nuclear hormone receptor was fused in frame with the LexA DNA-binding domain (LexA-DBD) and the VP16 activation domain (LexA-DBD:AR-LBD:VP16) generating an androgen receptor tripartite construct. The tripartite construct was transformed into S. cerevisiae. The fusion protein confers steroid-responsive transcription of a reporter gene β-galactosidase. To determine if other steroids could cross-react with the androgen-receptor ligand-binding domain, we tested if thyroid hormone, progesterone, and estrogen could induce transcription of the reporter through the androgen receptor tripartite. In addition, to determine if we could detect bioactivity from serum, extracted serum samples from several individuals were tested for androgen bioactivity. Serum samples were also tested for testosterone using standard radioimmunoassay (RIA) and liquid chromatography/mass spectrometry/ mass spectrometry (LC/MS/MS) methods. Results: Serum bioactivity showed good correlation with RIA serum testosterone levels (r = 0.94, n=36). In addition to testosterone, the bioassay was responsive to a number of weak and potent anabolic steroids including stanozol, nandrolone, and DHT; however, only non-physiological concentrations of estrogen and progesterone were able to activate the androgen reporter. In preliminary testing of random healthy females (n=32) using the androgen bioassay, an elevated level of androgen bioactivity was observed in several individuals. Two with high bioactivity had elevated levels of testosterone by LC/MS/MS. Retrospectively, all except one of the remaining individuals with high androgen bioactivity were on birth control pills. Conclusions: Although preliminary, these results suggest that the androgen bioassay can detect endogenous and anabolic steroid molecules circulating in the blood. Yeast bioassays may have broad utility in the area of biological actions of hormones in diagnostics and hormone disrupters.